Large contribution of recent photosynthate to soil respiration in tropical dipterocarp forest revealed by girdling. (5th December 2021) - Nottingham, Andrew T.; Cheesman, Alexander W.; Riutta, Terhi; Doughty, Christopher E.; Telford, Elizabeth; Huaraca Huasco, Walter; Svátek, Martin; Kvasnica, Jakub; Majalap, Noreen; Malhi, Yadvinder; Meir, Patrick; Arn Teh, Yit
Abstract: Tropical forests are the most productive terrestrial ecosystems, fixing over 40 Pg of carbon from the atmosphere each year. A substantial portion of this carbon is allocated below‐ground to roots and root‐associated micro‐organisms. However, there have been very few empirical studies on the dynamics of this below ground transfer, especially in tropical forests where carbon allocation processes are influenced by high plant species diversity. We used a whole‐stand girdling experiment to halt the below‐ground transfer of recent photosynthates in a lowland tropical forest in Borneo. By girdling 209 large trees in a 0.48 ha plot, we determined: (a) the contribution of recent photosynthate to root‐rhizosphere respiration and; (b) the relationships among the disruption of this below‐ground carbon supply, tree species composition and mortality. Mortality of the 209 trees was 62% after 370 days, with large variation among species and particularly high mortality within the Dipterocarpaceae (99%) and Fagaceae (100%) families. We also observed a higher risk of mortality following girdling for species with lower wood density. Soil CO2 emissions declined markedly (36 ± 5%) over 50 days following girdling in three of six monitored subplots. In the other three subplots there was either a marginal decline or no response of soil CO2 emissions to girdling. The decrease in soil CO2 efflux was larger in subplots with dominance of Dipterocarpaceae. Synthesis . Our results indicate high spatial variation in the coupling of below‐ground carbon allocation and root‐rhizosphere respiration in this tropical forest, with a closer coupling in forest dominated by Dipterocarpaceae. Our findings highlight the implications of tree species composition of tropical forests in affecting the dynamics of below‐ground carbon transfer and its release to the atmosphere. Abstract : Ringkasan: Hutan tropis adalah ekosistem terestrial yang paling produktif, menghasilkan sekitar 40 Pg karbon dari atmosfer setiap tahun. Sebilangan besar karbon ini diperuntukkan di bawah tanah untuk akar dan mikroorganisma yang berkaitan dengan akar. Walau bagaimanapun, terdapat sedikit kajian empirik mengenai dinamika pemindahan bawah tanah ini, terutama di hutan tropika di mana proses peruntukan karbon dimediasi oleh kepelbagaian spesies tumbuhan yang tinggi. Kami menggunakan eksperimen girdling utuh untuk menghentikan pemindahan fotosintesis baru‐baru ini di hutan tropika dataran rendah di Borneo. Dengan merangkai 209 pokok besar di sebidang 0.48 ha, kami menentukan: i) sumbangan fotosintesis baru‐baru ini untuk pernafasan akar‐rizosfera dan; ii) hubungan antara gangguan bekalan karbon bawah tanah ini, komposisi spesies pokok dan kematian. Kematian 209 pokok adalah 62% selepas 370 hari, dengan variasi yang besar di antara spesies dan terutamanya kematian yang tinggi dalam keluarga Dipterocarpaceae (99%) dan Fagaceae (100%). Kami juga mengamati risiko kematian yang lebih tinggi berikutan menyikat spesies dengan kepadatan kayu yang lebih rendah. Pelepasan CO2 tanah menurun dengan ketara (36 ± 5%) selama 50 hari berikutan menggelecek di tiga daripada enam subplot yang dipantau. Di tiga subplot yang lain terdapat penurunan marjinal atau tidak ada tindak balas pelepasan CO2 tanah terhadap girdling. Penurunan aliran masuk CO2 tanah lebih tinggi di subplot dengan dominasi Dipterocarpaceae. Sintesis. Hasil kajian kami menunjukkan variasi spasial yang tinggi dalam penggabungan alokasi karbon di bawah tanah dan respirasi akar‐rizosfera di hutan tropika ini, dengan gandingan lebih dekat di hutan yang dikuasai oleh Dipterocarpaceae. Hasil kajian kami menunjukkan implikasi komposisi spesies pokok hutan tropika dalam mempengaruhi dinamika pemindahan karbon di bawah tanah dan pembebasannya ke atmosfera.